Examination Of Social Study Teacher Candidate's Opinions On Creative Thinking Skills - Küçük, Emine; Kan, Çiğdem (Salim DURUKOĞLU, 2023)
The aim of this study is to determine the creative thinking skills of social studies teacher candidates and to examine the results in terms of various variables. This research, in which the scanning model was used, was prepared in line with the data obtained from a total of 190 students studying in the Department of Social Studies Education, Fırat University, Faculty of Education, in the 2019-2020 academic year. The data of the study were obtained by using the personal information form prepared to determine some personal characteristics of social studies teacher candidates and the creativity scale to determine their creative thinking levels. The obtained data were evaluated and analyzed using the SPSS 22.0 statistical package program. As a result of the research, the creative thinking skills of the social studies teacher candidates and their grade level, gender, parental education level, monthly income of the family, watching a discussion program, information It was determined that there was no significant relationship between variables such as watching the competition, solving puzzles, and frequency of reading newspapers and books. However, a significant difference was found in terms of taking pre-school education, participating in cultural activities, doing sports, watching entertainment programs, watching documentaries and TV series, and the presence of those interested in music in the family.

Bu araştırmanın amacı, sosyal bilgiler öğretmen adaylarının yaratıcı düşünme becerilerinin belirlenmesi ve ortaya çıkan sonuçların çeşitli değişkenler açısından incelenmesidir. Tarama modelinin kullanıldığı bu araştırma, 2019-2020 eğitim öğretim yılında Fırat Üniversitesi, Eğitim Fakültesi, Sosyal Bilgiler Eğitimi Bölümünde öğrenim gören toplam 190 öğrenciden elde edilen veriler doğrultusunda hazırlanmıştır. Araştırmanın verileri, sosyal bilgiler öğretmen adaylarının bazı kişisel özelliklerini tespit etmek için hazırlanan kişisel bilgi formu ile yaratıcı düşünme düzeylerini saptamak için yaratıcılık ölçeği kullanılarak elde edilmiştir. Elde edilen veriler, SPSS 22.0 istatistik paket program aracılığıyla değerlendirilmiş ve çözümlemeleri yapılmıştır. Araştırma sonucunda sosyal bilgiler öğretmen adaylarının yaratıcı düşünme becerileri ile sınıf seviyesi, cinsiyet, anne-baba eğitim durumu, ailenin aylık geliri gibi değişkenler arasında anlamlı bir ilişki olmadığı belirlenmiştir. Ancak okul öncesi eğitim alma, kültürel etkinliklere katılma, spor yapma, eğlence programları, belgesel, dizi film izleme ve ailede müzikle ilgilenenlerin varlığı değişkenleri açısından anlamlı bir farklılık bulunmuştur.
Sosyal Bilgiler Öğretmen Adaylarının Yaratıcı Düşünme Becerilerine İlişkin Görüşlerinin İncelenmesi